A Policy Implementation Review of the Free Nutritious Meal (MBG) Program - Firre An Suprapto; Editha Praditya; Reffi Marizka Dewi; Wignyo Adiyoso (Pusbindiklatren Bappenas, 2025)
This study evaluates the early implementation of Indonesia’s Free Nutritious Meal Program (Makan Bergizi Gratis/MBG) through a multidimensional policy review. Anchored in health, education, economic, and socio-environmental aspects, the study synthesizes national data, international best practices, and case comparisons with similar programs in Brazil, India, and Finland. The findings highlight that while MBG has significant potential to improve human capital, its direct impact on stunting and anemia remains unverified due to limited targeting of the first 1,000-day window and the absence of formal outcome tracking. The program demonstrates positive signs of improved school attendance and MSME engagement, yet faces implementation challenges related to food safety, logistics, and regulatory coherence. A SWOT analysis is employed to identify key strategic levers, indicating that realignment of program focus, multisectoral integration, and enhanced monitoring are essential to achieving the MBG's long-term objectives. The study offers critical insights for policymakers to refine MBG and ensure its alignment with national development goals and global nutrition commitments.